2002
DOI: 10.1128/iai.70.8.4132-4141.2002
|View full text |Cite
|
Sign up to set email alerts
|

Roles of p38 Mitogen-Activated Protein Kinase, NF-κB, and Protein Kinase C in Proinflammatory Cytokine mRNA Expression by Human Peripheral Blood Leukocytes, Monocytes, and Neutrophils in Response toAnaplasma phagocytophila

Abstract: Anaplasma phagocytophila, an obligately intracellular bacterium of granulocytes, causes human granulocytic ehrlichiosis. Within 2 h after addition of A. phagocytophila, interleukin-1␤ (IL-1␤), tumor necrosis factor alpha (TNF-␣), and IL-6 mRNAs are induced in human peripheral blood leukocytes (PBLs) or monocytes in vitro. However, neutrophils generate only IL-1␤ mRNA. In the present study, signaling pathways for induction of these three cytokines were examined. TNF-␣ and IL-6 mRNA expression by PBLs was inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 54 publications
3
39
0
Order By: Relevance
“…We demonstrated upregulation of CD11b, down-modulation of L-selectin (CD62L) (13), and prolonged degranulation in A. phagocytophilum-infected neutrophils (12), and these phenomena could be mediated in part by p38 MAPK as well. Kim and Rikihisa also examined p38 MAPK in human neutrophils infected by A. phagocytophilum and concluded that this pathway was not activated (27). The reasons for these discrepant results are unclear; however, the uniform production from A. phagocytophilum-infected neutrophils of chemokines known to stimulate p38 MAPK and the activation of this pathway in neutrophils by other bacterial components, such as LPS (4), argue against its absence.…”
Section: Vol 73 2005 P38 Mapk In a Phagocytophilum-infected Neutromentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated upregulation of CD11b, down-modulation of L-selectin (CD62L) (13), and prolonged degranulation in A. phagocytophilum-infected neutrophils (12), and these phenomena could be mediated in part by p38 MAPK as well. Kim and Rikihisa also examined p38 MAPK in human neutrophils infected by A. phagocytophilum and concluded that this pathway was not activated (27). The reasons for these discrepant results are unclear; however, the uniform production from A. phagocytophilum-infected neutrophils of chemokines known to stimulate p38 MAPK and the activation of this pathway in neutrophils by other bacterial components, such as LPS (4), argue against its absence.…”
Section: Vol 73 2005 P38 Mapk In a Phagocytophilum-infected Neutromentioning
confidence: 99%
“…MAPK activation was previously shown in monocytes, but not neutrophils, exposed to A. phagocytophilum (27). However, given the known regulatory function of p38 MAPK in apoptosis, this pathway requires a more in-depth examination of A. phagocytophilum-infected neutrophils.…”
mentioning
confidence: 99%
“…15,16) In response to bacteria such as Anaplasma spp., Ehrlichia spp., Salmonella typhimurium and Pseudomonas aeruginosa, neutrophils enhance the transcript levels and/or protein secretion of IL-1/, IL-6, IL-8, macrophage inflammatory protein-1 (MIP-1) and/or tumor necrosis factor-(TNF-). [17][18][19][20] Furthermore, numerous neutrophils accumulate in areas infected by fungi. 21) Freshly isolated neutrophils secrete IL-8 in response to heatkilled S. cerevisiae and C. albicans, and MIP-1 to heat-killed C. albicans, albeit to a lower extent, compared to bacterial responses.…”
mentioning
confidence: 99%
“…Likewise, there are reports in the mammalian literature describing signalling pathway differences depending on the agonist used (Yum et al, 2001;Strassheim et al, 2004). As we have seen with heterophils, regulation of interleukin-6 and other inflammatory cytokines in mammalian cells is also mediated by NF-kB (Kim & Rikihisa, 2002;Cloutier et al, 2007;Requena et al, 2009;Cao et al, 2010;Khalaf et al, 2010), and interleukin-8 production is regulated more so by AP-1 in T cells (Khalaf et al, 2010), and NF-kB in monocytes (Vitiello et al, 2004). Additionally, deficiencies in AP-1 proteins are associated with increased susceptibility to S. typhimurium (Maruyama et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…Phosphorylation of p38 and JNK influences downstream cytokine/chemokine production (Kim & Rikihisa, 2002;Cloutier et al, 2003Cloutier et al, , 2007. Induction of pro-inflammatory cytokines and chemokines by neutrophils is dependent on the activation of p38 (Cloutier et al, 2007), while JNK has a lesser role in inflammatory cytokine/chemokine production (Cloutier et al, 2003).…”
Section: Discussionmentioning
confidence: 99%